Development of novel multiferroic composites based on BaTiO3 and hexagonal ferrites - Karpinsky,DV; Selezneva,EK; Bdikin,K; Figueiras,F; Kamentsev,KE; Fetisov,YK; Pullar,RC; Krebbs,J; Alford,NM; Kholkin,AL (2009)
New multiferroic composite ceramics with the general formula (x)Ba(Sr)Fe12O19-(1-x)BaTiO3 (x=0.1, 0.5) were synthesized via a simple solid-state reaction technique. Crystal structure analysis performed for such materials revealed the presence of two crystalline phases pertinent to the initial composite components. X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to assess the crystallinity, microstructure, and local magnetoelectric interactions between ferroelectric and ferromagnetic grains. Magnetic measurements revealed that the saturation magnetization is proportional to the volume fraction of ferrite phase. Dielectric studies demonstrated strong frequency relaxation due to space charge polarization and high conductivity loss making macroscopic magnetoelectric measurements difficult. Novel nanoscale magnetoelectric effect observed by AFM is discussed. © 2009 Materials Research Society.